Living with Loss: study protocol for a randomized controlled trial evaluating an internet-based perinatal bereavement program for parents following stillbirth and neonatal death - Siobhan A. Loughnan; Frances M. Boyle; David Ellwood; Sara Crocker; Ann Lancaster; Chrissie Astell; Julie Dean; Dell Horey; Emily Callander; Claire Jackson; Antonia Shand; Vicki Flenady (Trials, 2022)
Abstract Background Stillbirth and neonatal death are devastating pregnancy outcomes with long-lasting psychosocial consequences for parents and families, and wide-ranging economic impacts on health systems and society. It is essential that parents and families have access to appropriate support, yet services are often limited. Internet-based programs may provide another option of psychosocial support for parents following the death of a baby. We aim to evaluate the efficacy and acceptability of a self-guided internet-based perinatal bereavement support program “Living with Loss” (LWL) in reducing psychological distress and improving the wellbeing of parents following stillbirth or neonatal death. Methods This trial is a two-arm parallel group randomized controlled trial comparing the intervention arm (LWL) with a care as usual control arm (CAU). We anticipate recruiting 150 women and men across Australia who have experienced a stillbirth or neonatal death in the past 2 years. Participants randomized to the LWL group will receive the six-module internet-based program over 8 weeks including automated email notifications and reminders. Baseline, post-intervention, and 3-month follow-up assessments will be conducted to assess primary and secondary outcomes for both arms. The primary outcome will be the change in Kessler Psychological Distress Scale (K10) scores from baseline to 3-month follow-up. Secondary outcomes include perinatal grief, anxiety, depression, quality of life, program satisfaction and acceptability, and cost-effectiveness. Analysis will use intention-to-treat linear mixed models to examine psychological distress symptom scores at 3-month follow-up. Subgroup analyses by severity of symptoms at baseline will be undertaken. Discussion The LWL program aims to provide an evidence-based accessible and flexible support option for bereaved parents following stillbirth or neonatal death. This may be particularly useful for parents and healthcare professionals residing in rural regions where services and supports are limited. This RCT seeks to provide evidence of the efficacy, acceptability, and cost-effectiveness of the LWL program and contribute to our understanding of the role digital services may play in addressing the gap in the availability of specific bereavement support resources for parents following the death of a baby, particularly for men. Trial registration Australian New Zealand Clinical Trials Registry, ACTRN12621000631808 . Registered prospectively on 27 May 2021.